Quality Management and Formalization in Social Service Organizations - A Survey on Home-Based Family Intervention Services - Christof Beckmann; Andreas Schaarschuch; Hans-Uwe Otto; Mark Schrödter (Social Work & Society, 2007)
Although the effects of quality management on social work are still widely unexplored, critics suspect that it will lead to a negative standardization of working conditions, whereas supporters of quality management hope for a greater transparency and effectiveness of service delivery. This article reports on a survey of 30 managers, 261 professionals, and 435 families in 30 family intervention service organizations. It uses cluster analysis to explore the relationship between quality management and different forms of work formalization. Results showed that working conditions generally are enabling for professional practice, but differences exist between what is called here a managerialist machine bureaucracy, an atomistic professional organization, and a collegiate professional organization.